The Mongolia navy all at sea - Journeyman Pictures (United Kingdom : Journeyman Pictures, 2001)
This documentary is about navy at the world's biggest landlocked country (Mongolia), which comprises one boat and seven sailors.
Keywords: Mongolia -- Navy